Simulation of micro hydro power based on river configuration at river downstream - Siti Nor Suziyana, Dollah (2013)
Micro hydro power convert potential energy of water into electricity and it a clean source. The project present about Simulation of Micro Hydro Power based on river configuration at river downstream. The objectives of this project to simulate flow of downstream river for different Micro hydro power, to determine the performance and efficiency of micro hydro power in downstream river and to determine the availability of hydroelectric in rural areas. This project is focused on downstream river where the velocity, pressure and topology data is to be determined. The place that used for this project is Sungai Pahang. In this project just used two software, it is SolidWorks 2012 and ANSYS (CFX). Simulations have been done with two different turbine of micro hydro power, the first turbine is Propeller and the second is Tidal turbine. Between the two turbines the performance of Propeller turbine are good compared to the tidal turbine. It is because the toque of Propeller is higher compared to the tidal. The torque is 17.295Nm and 11.901Nm. As the conclusion propeller turbine are beater compare to the tidal turbine.